Pengaruh Inovasi Pengelola Dan Adaptasi Pengelola Terhadap Kualitas Pelayanan Ruang Publik Terpadu Ramah Anak (Rptra) Di Kelurahan Cipedak Kecamatan Jagakarsa Jakarta Selatan Provinsi Dki JakartaTahun 2025 - Suliyah; Indah Wahyu Maesarini (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
Public services are mandatory for the government to fulfill the rights of citizens. The quality of public services includes key dimensions such as Tangible (Physical Evidence), Reliability, Responsiveness, Assurance, and Empathy, which are manifested through transparency, accountability, simplicity of procedures, equal rights (non-discriminatory), and community participation, thus becoming a crucial point in determining whether innovation and adaptation by managers will improve service quality. The research method used quantitative data collection techniques with questionnaires and data analysis using SPSS 2025. The research location was the Child-Friendly Integrated Public Space (RPTRA) in the Cipedak sub-district of Jagakarsa, South Jakarta. RPTRA stands for Ruang Publik Terpadu Ramah Anak (Integrated Child-Friendly Public Space), which is a public open space provided by the Jakarta provincial government as a safe and comfortable place for children to play, for residents to socialize, and for empowerment, education, and educational information communication (KIE) activities, as well as a forum for social interaction among residents. The results of this study conclude that management innovation has a positive and significant effect on service quality by 25.2%. Management adaptation has a positive and significant effect on service quality by 32%. Managerial innovation and adaptation have a positive and significant impact on service quality by 34.1%, while the remaining 65.9% is influenced by other variables not yet studied by the researcher. This research is expected to make a meaningful contribution to the field of public administration and be able to solve practical problems so that it can be applied to a wider population, and its recommendations can be followed up by policy makers.